2005
DOI: 10.4319/lo.2005.50.3.0743
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of aquatic refugia between flow pulses in a dryland river system(Cooper Creek, Australia)

Abstract: In many dryland rivers with intermittent flow, relatively deep segments of the river channel serve as refugia for aquatic life during protracted intervals between flows. Semipermanent channel segments are known as waterholes in the semiarid Cooper Creek system of western Queensland. Fractional water loss by evaporation was estimated in 15 Cooper waterholes from the increase in conservative ion (Na ϩ and Cl Ϫ ) concentrations and independently from evaporative fractionation of oxygen and hydrogen isotopes in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 27 publications
5
105
0
Order By: Relevance
“…In the river pools of some arid zones, water quality deteriorates as water volume declines during drought periods, even in permanent wetlands, and especially where water levels are controlled by surface water flows and/or where saline groundwater intrudes when water levels are low (Costelloe et al 2005;Hamilton et al 2005). Such pools can experience raised salinity and temperature, concentration of nutrients and increased solar radiation as pools contract away from banks, with subsequent problems associated with algal blooms (Lake 2003).…”
Section: Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the river pools of some arid zones, water quality deteriorates as water volume declines during drought periods, even in permanent wetlands, and especially where water levels are controlled by surface water flows and/or where saline groundwater intrudes when water levels are low (Costelloe et al 2005;Hamilton et al 2005). Such pools can experience raised salinity and temperature, concentration of nutrients and increased solar radiation as pools contract away from banks, with subsequent problems associated with algal blooms (Lake 2003).…”
Section: Diversitymentioning
confidence: 99%
“…These impacts have well-known effects on aquatic invertebrates, including reduced species richness (reviewed in Lake 2003). Hamilton et al (2005) suggested that waterholes maintained by fresh groundwater would be 'exceptionally important' refugia in the Cooper Creek system of the Lake Eyre Basin. By contrast, in the Pilbara, pools maintained by fresh hyporheic or spring flows are not unusual and water quality tends to remain high during dry periods.…”
Section: Diversitymentioning
confidence: 99%
“…Here, biotic interactions, including competition for limited food resources and predation from waterbirds, are concentrated. Species become locally extinct as their ecological tolerances are exceeded, with final population persistence determined by the habitat characteristics of an individual refuge, the rate of evaporative water loss, the resilience of the taxa present and disturbance intensity (Closs and Lake, 1996;Arthington et al, 2005;Hamilton et al, 2005). If a drought is particularly severe or protracted, loss of entire fish communities may occur at large spatial scales (e.g., river reaches).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the temporary nature of many wetlands, and the resultant variability of physico-chemical factors, the biota have evolved unique features and life-cycle adaptations that enable them to persist over dry intervals (e.g. use of deep channel segments as aquatic refugia, Walker et al, 1995;Sheldon et al, 2002;Hamilton et al, 2005). Arid/semi-arid wetlands show faunal diversity as high as, or greater than that in many temperate and tropical wetlands (Williams, 1998a,b).…”
Section: Introductionmentioning
confidence: 99%